Analysis of the Use of Aviobridge to Improve on Time Performance at Jenderal Ahmad Yani International Airport Semarang - Anisa Mega Utami; Walid Jumlad (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The time factor is a crucial factor in airlines. So that the timeliness of on time performance (OTP) is important in the world of aviation. This study aims to determine the use of aviobridge and the impact of using aviobridge in increasing on time performance at Jenderal Ahmad Yani International Airport Semarang. This research uses a quantitative descriptive method. The population and sample of this study are monthly airline data including flight schedule data, actual airline data, on time airline data, and airline data using aviobridge. The data analysis carried out consisted of reduction, data presentation, and drawing conclusions. The results of this study indicate that there is an influence from the use of aviobridge on on time performance at General Ahmad Yani International Airport Semarang with H1 accepted because there are significant results from the two variables. These results show that in December 2022 the total average use of aviobridge was 155.7%, which affected delays with an average of 22% and a ratio of 1:1.13.